2015
DOI: 10.1002/cbin.10406
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of telomeres in the tobacco meiotic nuclei during cytomixis

Abstract: Cytomixis is the migration of nuclei from one cell to another in higher plants, most frequently observable during microsporogenesis, which has a potential evolutionary significance. Currently, a major challenge is to label the chromatin migrating between cells to clarify its further fate. We have for the first time succeeded in visualizing the telomeric chromatin regions in the nuclei migrating between cells using fluorescent in situ hybridization. It has been shown that the telomeric signals in tobacco micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Using electron and fluorescence microscopy, transgenic plants expressing H2B‐CFP as well as FISH‐method for marking telomeric repeats of chromosomes, it was shown that the nuclear envelope and chromatin remain intact in cytomictic migrations (Wang et al, ; Liu et al, ; Mursalimov and Deineko, ; Mursalimov et al, ,). In these experiments the micronuclei and migrating chromatin emitted multiple telomeric signals, which were either localized in clusters or dispersed, depending upon the meiosis stage (Mursalimov et al, ). Moreover, the specific localization of telomeric signals suggested that the bivalent organization of the chromosomes was retained during migration.…”
Section: Peculiarities Of Nuclear Interactions and Nuclear Translocationmentioning
confidence: 99%
See 1 more Smart Citation
“…Using electron and fluorescence microscopy, transgenic plants expressing H2B‐CFP as well as FISH‐method for marking telomeric repeats of chromosomes, it was shown that the nuclear envelope and chromatin remain intact in cytomictic migrations (Wang et al, ; Liu et al, ; Mursalimov and Deineko, ; Mursalimov et al, ,). In these experiments the micronuclei and migrating chromatin emitted multiple telomeric signals, which were either localized in clusters or dispersed, depending upon the meiosis stage (Mursalimov et al, ). Moreover, the specific localization of telomeric signals suggested that the bivalent organization of the chromosomes was retained during migration.…”
Section: Peculiarities Of Nuclear Interactions and Nuclear Translocationmentioning
confidence: 99%
“…It is believed that genetic control of meiotic cytomixis involves meiotic genes activity of which is regulated by environmental factors through signal transduction (Bedi, ; Kaul and Murthy, ; Bellucci et al, ; Lattoo et al, ; Mandal et al, ). Many of the authors emphasize the potential evolutionary significance of cytomixis (Malallah and Attia, ; Lattoo et al, ; Kumar and Singhal, , ; Ghaffari, ; Singhal et al, ,; Pierre and de Sousa, ; Malik and Gupta, ; Lone and Lone, ; de Storme and Geelen, ; Mursalimov et al, , ).…”
Section: Introductionmentioning
confidence: 99%
“…8,[13][14][15][16] On transgenic tobacco lines showed that cytomictic chromatin retains not only its physical, but functional properties as well. [17][18][19] The chromosomal polymorphism of microsporocytes and pollen grains, the existence of a large variety of natural polyploid cytotypes in many cytomictic species as well as fact that cytomixis is attributed to male generative sphere and "male-driven" evolution allow us to consider cytomixis as one of the mechanisms to increase genetic diversity and speciation in plants. 2,[8][9][10][11][12][16][17][18][20][21][22] The wide occurrence of cytomixis in terrestrial plants testifies its being involved in the important genomic reorganization processes, which allow its carriers to be maintained due to natural selection process.…”
Section: Introductionmentioning
confidence: 99%
“…Наиболее известные исследования цитомиксиса связаны с микроспорогенезом покрытосеменных, где он наблюдается преимущественно в ранней профазе первого деления синхронно с ключевыми событиями мейоза. Если цитомиксис подпадает под генетическую регуляцию мейоза, то мигрирующий хроматин, при условии сохранения его интактности и функциональной активности [1,2], может встраиваться в геном клетокреципиентов и участвовать в перестройке генома микроспороцитов. Это косвенно подтверждается хромосомным полиморфизмом микроспороцитов и существованием широкого ряда природных полиплоидных цитотипов у многих видов растений, которым свойственен цитомиксис [3][4][5].…”
unclassified